2016
DOI: 10.1002/pc.24037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing methods on electrical percolation and electromagnetic shielding of PC/MWCNTs nanocomposites

Abstract: Nanocomposites of polycarbonate (PC)/multiwalled carbon nanotubes (MWCNTs) containing 0.5-3 wt% of MWCNTs were prepared via two methods of melt mixing and solution mixing. The effect of CNT content and processing methods on electrical and electromagnetic properties of nanocomposite samples were investigated. TEM microphotographs revealed that the PC/ MWCNT composites prepared by the solution method, have better dispersion and distribution of CNTs in the PC matrix. Electrical measurements indicated an electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…22 The percolation threshold for the electrical conductivity in these composites is closely related to the dispersion state of carbon nanotubes, 248,300-303 alignment, 304,305 dimensions (e.g., length and diameter) of carbon nanotubes, 300,303,[306][307][308][309][310] degree of modication of the surface of carbon nanotubes, [310][311][312] type of polymers, 313 and composite processing method. 300,[314][315][316] The percolation threshold is strongly dependent upon the degree of the dispersion of carbon nanotubes. Additionally, alignment of carbon nanotubes plays an important role in determining the electrical conductivity of the nanocomposite and its percolation threshold.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…22 The percolation threshold for the electrical conductivity in these composites is closely related to the dispersion state of carbon nanotubes, 248,300-303 alignment, 304,305 dimensions (e.g., length and diameter) of carbon nanotubes, 300,303,[306][307][308][309][310] degree of modication of the surface of carbon nanotubes, [310][311][312] type of polymers, 313 and composite processing method. 300,[314][315][316] The percolation threshold is strongly dependent upon the degree of the dispersion of carbon nanotubes. Additionally, alignment of carbon nanotubes plays an important role in determining the electrical conductivity of the nanocomposite and its percolation threshold.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…It can be concluded from the above discussion that the rheological percolation threshold can be achieved at lower concentration of CNTs as compared to electrical percolation threshold. However, for PS/MWCNTs composites, it was observed that the rheological percolation threshold (between 0.9 wt% and 1 wt% of CNTs) was achieved at higher concentration of CNTs as compared to its electrical percolation threshold …”
Section: Relationship Between Electrical and Rheological Percolation mentioning
confidence: 99%
“…The value of electrical percolation for melt-mixed PS/MWCNTs composite was observed to be between 0.5 wt% and 0.6 wt% of MWCNT, [13] for PC/MWCNTs it was around 0.84 wt% of MWCNTs, [14] between 1 wt% and 2 wt% of MWCNTs for PP/MWCNTs composites, [15] and above 2.5 wt% of MWCNTs for PA6/MWCNTs. [16] Apart from interfacial interaction factor, the second most important factor which dictates the extent of dispersion of MWCNTs in polymer matrix is the melt viscosity of the matrix.…”
Section: Various Aspects Of Polymer Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interference of EM radiations can disturb the routine performance or cause the complete failure of equipments . Thus, electromagnetic interference (EMI) shielding of radio frequency radiation is still a serious concern for modern society . In this regard, developing cost effective and lightweight EMI shielding materials to minimize EMI have received considerable attention in recent years.…”
Section: Introductionmentioning
confidence: 99%